Discrete Ordinates Method and the Examination of Some Benchmark Problems - Sağ, Semiha (İstanbul Kültür Üniversitesi Yayınları, 2003)
In this study wellknown numerical solution method of neutron transport equation, Discrete Ordinates Method, has been introduced and using some Benchmark problems the ray-effect distortions observed in the method have been examined. Fort his purpose, TWOTRAN-II code has been chosen and executed for sample problems. Finally, the effectiveness of the method has been discussed in detail.

Bu çalışmada, nötron transport denkleminin çok tanınan bir çözüm yöntemi. Kesikli Ordinatlar Yöntemi tanıtılmış ve Benchmark problemleri kullanarak metodda gözlenen ışın-etkisi bozulmaları incelenmiştir. Bu amaçla TWOTRAN-II kodu seçilmiş ve bazı örnek problemler için koşulmuştur. Sonuçta, yöntemin etkinliği ayrıntılı bir biçimde tartışılmıştır.
Keywords: discrete ordinates method; neutron transport equation; deterministic numerical method; benchmark problem; ray-effect; ayrık koordine yöntem; nötron transport denklemi; deterministik sayısal yöntem; gösterge sorunu; ray-etkisi